The Effect of Deep Breathing Relaxation on Stress Levels in Hypertension Patients - Diah Ayu Puspa Sari; Ika Mustafida; Enni Juliani (Genius Journal, 2025)
Introduction: Hypertension is a significant risk factor for morbidity and mortality associated with cardiovascular disease. The relationship between hypertension and stress is bidirectional, where hypertension can trigger stress through physiological and emotional response mechanisms. Stress activates the nervous system by increasing the production of hormones such as cortisol and adrenal. Objective: This study aims to analyze the effect of deep breathing relaxation on stress levels of hypertension patients. Method: This study used a quasi eksperiment one-group Pretest-Posttest design conducted in May 2025 at the Tambora District Health Center, West Jakarta. The sample size was 34 with a purposive sampling technique. Stress levels were measured using the Depression Anxiety Stress Scale (DASS-21) questionnaire. The intervention provided was deep breathing relaxation for 14 days. Result: The results showed that the average stress level before the intervention 21.71 in the moderate category, then after the intervention the stress level score decreased to 10.41 in the normal category. The Wilcoxon test showed a p-value of 0.00 (p<0.05), indicating a significant difference between stress levels before and after deep breathing relaxation. Conclusion: This study concluded that deep breathing relaxation is effective in reducing stress levels in hypertension patients and can be used as a non-pharmacological intervention for hypertension patients that is easily implemented in primary health care.